How Jewish Orthodoxy Became a State: Isaac Breuer and the Invention of the Statist Theocracy - Ben Ami, Itamar (Harvard theological review, 2023)
This article traces the incorporation of the modern state and the notion of sovereignty into Jewish Orthodox thought, culminating in the idea that the role of Orthodoxy is to establish a statist theocracy. Unlike narratives that emphasize the continuation of theocratic thought from ancient to modern Judaism on the one hand, and the relationship between religious Zionism and contemporary forms of Jewish theocracy on the other, my research reveals a fundamentally anti-Zionist, ultra-Orthodox layer in the doctrine of statist theocracy, through a novel reading of the early writings of one of the leaders of Agudath Israel, Isaac Breuer (1883-1946). During the 1920s, Breuer coined terms such as Gottesstaat and Torastaat, which informed broader theocratic discussions into the 1930s. The article examines the intellectual history of this discourse and the grammar of this doctrine, identifying in it ultra-Orthodox reasoning such as an aversion to secularism and modern nationalism, resistance to a redemptive, kookian philosophy of history, and adherence to the "Rule of Torah."